1998
DOI: 10.1007/bf02893804
|View full text |Cite
|
Sign up to set email alerts
|

Body images and obesity risk among Black females: A review of the literature

Abstract: The prevalence of obesity among Black women has reached epidemic proportions. Some researchers have suggested that the body images of Black females may contribute to their high risk for obesity by inhibiting motivation for weight control. While a number of empirical studies have examined the body images of Black females, findings are complex and at times, inconsistent. For example, some studies show that Black females consider overweight bodies more attractive, while other studies show that Black females prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
215
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(229 citation statements)
references
References 68 publications
12
215
2
Order By: Relevance
“…Differences in body image between Blacks and Whites, particularly among women, may be a factor contributing to the higher rates of obesity in Blacks (Flynn and Fitzgibbon, 1998). For example, Black women indicate less disapproval of overweight women than do White women (Hebl and Heatherton, 1998).…”
Section: Neighborhoods Body Mass Index and Ethnicitymentioning
confidence: 99%
“…Differences in body image between Blacks and Whites, particularly among women, may be a factor contributing to the higher rates of obesity in Blacks (Flynn and Fitzgibbon, 1998). For example, Black women indicate less disapproval of overweight women than do White women (Hebl and Heatherton, 1998).…”
Section: Neighborhoods Body Mass Index and Ethnicitymentioning
confidence: 99%
“…Correspondence to: Angela Odoms-Young.Nevertheless, whereas early studies discussed black women's body image as a cultural asset, in the context of the growing concern over the rising prevalence of obesity, it has been suggested that body image norms in the black community may place black women at risk for overweight (Flynn & Fitzgibbon, 1998). For example, Bennett and Wolin (2006) report that obese black women were over three times as likely as their white counterparts to believe they were at "about the right weight" (p.40).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the perception of ideal body size varies with culture, ethnicity, educational level and socioeconomic group [7][8][9][10][11] and can influence the development of obesity. 12,13 In Western societies, thinness is associated with self-control, elegance, youthfulness and attractiveness, and women of higher socioeconomic groups are less likely to be obese. 9 The situation in some developing countries appears to be the opposite, and some authors 12,14,15 conclude that obesity is admired and seen as sexually desirable, and a symbol of social success and wealth in countries where economic resources are scarce.…”
Section: Introductionmentioning
confidence: 99%